The EFFECT OF FEE BASED INCOME, OPERATIONAL COSTS ON OPERATIONAL INCOME (BOPO) AND DISTRIBUTION OF CREDIT ON PROFITABILITY (ROA) IN. BANK BJB, Tbk PERIOD 2015 - 2020 - Lismadonna Br. Pohan; Nunung Nurhasanah; Didit Supriyadi (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aims to provide empirical evidence about the effect of fee-based income, Operational Expenses on Operational Income (BOPO), and credit distribution on profitability (ROA) of Bank BJB, Tbk. The research sample used is from 2015 - 2020. The method of analysis used is multiple linear regression with the classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results showed that the fee-based income variable had a significant and positive effect on the profitability of Bank BJB, Karawang Branch. Meanwhile, BOPO and lending had a significant but negative effect on profitability. Simultaneously fee-based income, Operating Expenses on Operating Income (BOPO), and credit distribution have a significant effect on the profitability of Bank BJB Karawang Branch for the period 2015 to 2020.